Lamellar macular defects: are degenerative lamellar macular holes truly degenerative? - Pertile, Grazia; Iacovello, Daniela; Maraone, Giorgia; Bottega, Elisa; Guerriero, Massimo; Maggio, Emilia (Frontiers in Medicine, 2023)
Purpose: To investigate morpho-functional changes after surgical treatment for ERM foveoschisis or lamellar macular hole (LMH), and to evaluate whether the two entities are associated with different healing processes and long-term outcomes. Design: Retrospective interventional case series. Methods: A total of 56 eyes, treated for lamellar macular defects and followed up for 24 months, were enrolled. The eyes were divided into 2 groups: 34 with ERM foveoschisis and 22 with LMH. Changes in the following features were evaluated and compared between the two groups: best-corrected visual acuity (BCVA), external limiting membrane (ELM) and ellipsoid zone (EZ) defects, central foveal thickness (CFT), and autofluorescence (FAF) diameter and area. Results: After surgery, progressive BCVA improvement was observed with no significant difference between the two groups (p-value:0.06). An increased number of eyes with intact outer-retinal layers was found both in the ERM foveoschisis and LMH groups. FAF diameter and area decreased significantly throughout the FU with no significant difference between the two groups (p-value: 0.2). Conclusion: In the present study, significant functional and microstructural improvements were observed after surgery for both ERM foveoschisis and LMH, demonstrating considerable repair potential in both types of lamellar defects. These findings question the true “degenerative” nature of LMH.